Fig. 4. Methyl-3 in Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
Fig. 4. Methyl-3-orsellinate and 6-methylsalicylic acid biosynthesis pathway according to Legaz et al. (2011). Cyclisation is catalyzed by the cyclase subunit of two different PKS with or without a methyl transferase subunit. Published as part of Elshobary, Mostafa E., Becker, Michael G., Kalichuk, Jenna L., Chan, Ainsley C., Belmonte, Mark F. & Piercey-Normore, Michele D., 2018, Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection, pp. 142-150 in Phytochemistry 156 on page 146, DOI:10.1016/j.phytochem.2018.09.011, http://zenodo.org/record/10484507